Аналіз блокчейн-транзакцій: комплексний огляд застосувань, завдань та методів - Dorogyy, Yaroslaw; Kolisnichenko, Vadym (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2023)
Blockchain transaction analysis is a powerful tool to gain insights into the actions and conduct of participants within blockchain networks. This article aims to extensively examine the applications, tasks, and methods associated with blockchain transaction analysis. We look at various uses of transaction analysis, ranging from its instrumental role in blockchain development to its pivotal significance in the field of criminal investigations. By leveraging common techniques and technologies employed in conducting such an analysis, we unlock hidden insights and uncover information that is not visible at first look. This article offers a wide-ranging perspective on the profound significance of blockchain transaction analysis while shedding light on its key role within the cryptocurrency industry and its wide-ranging applications beyond.